1955
DOI: 10.3367/ufnr.0056.195508c.0531
|View full text |Cite
|
Sign up to set email alerts
|

Таммовские Связанные Состояния Электронов На Поверхности Кристалла И Поверхностные Колебания Атомов Решётки

Abstract: Т. LVI, вып. 4 УСПЕХИ ФИЗИЧЕСКИХ НАУКВ первой части статьи даётся обзор последовательных этапов развития теории таммовских поверхностных состояний электронов. Во второй части рассматриваются явления, в которых поверхност-ные состояния электронов играют существенную роль, и приводятся экспериментальные доказательства действительного существования этих состоякиЯ в реальных кристаллах. В третьей части статьи излагается теория поверхностных колебаний кристаллической ре-шётки, которая математически близка и генетич… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1960
1960
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…(1) and (2), where vector H substitutes for vector B, permittiv ity ε 2 substitutes for ε 1 , and field equations have the form (15) Using the approach developed in [46] to describe the coupled Tamm states on a crystal surface, we rep resent the fields in the region y > Nd as the superposi tion of incident and reflected waves, (20) where k is the Bloch wavenumber [47], the first terms in Eqs. (19) and (20) correspond to the fields of the wave incident on the interface y = Nd, and the second terms correspond to the fields of the wave reflected from the interface y = Nd.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…(1) and (2), where vector H substitutes for vector B, permittiv ity ε 2 substitutes for ε 1 , and field equations have the form (15) Using the approach developed in [46] to describe the coupled Tamm states on a crystal surface, we rep resent the fields in the region y > Nd as the superposi tion of incident and reflected waves, (20) where k is the Bloch wavenumber [47], the first terms in Eqs. (19) and (20) correspond to the fields of the wave incident on the interface y = Nd, and the second terms correspond to the fields of the wave reflected from the interface y = Nd.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…Let us write such a dependence of the electron potential energy on the coordinate y as follows: (1) where d is the structure period and δ(y) is the Dirac delta function. The electron wave function ψ in the problem under consideration satisfies the time inde pendent Schrödinger equation (2) where ប is Planck's constant, m is the electron mass, and E is the total electron energy. In the region y < 0, the solution to wave equation (2) is given by (3) where κ = /ប.…”
Section: Problem Statement and Basic Equationsmentioning
confidence: 99%
“…In [1], within the Kronig-Penney approximation, it was shown that bound electronic states can exist at the one dimensional lattice boundary, if the electron energy falls within the band gap of an infinite one dimensional lattice and is lower than its potential energy in the external space. From the time of the the oretical prediction of SESs, a large number of works were devoted to the study of their properties (see, e.g., [2][3][4][5][6][7] and references therein). Interest in SESs is caused by their ability to affect physical properties of crystalline solids.…”
Section: Introductionmentioning
confidence: 99%
“…2 These results are summarized by I. M. Lifshitz and S. I. Pekar (1955) for nonpolar lattice vibrations. 3 A review 3 shows that the theory of surface electronic states is deeply analogous with the theory of surface vibrations of crystal lattice atoms. In the one-dimensional case one of the branches of the energy spectrum transitions into Rayleigh branches, while others form surface optical branches.…”
mentioning
confidence: 99%